Differences in disease severity and prognosis of exercise-induced right-to-left shunt between idiopathic pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension patients - Wang, Shang; Guo, Zi-Yan; Sun, Xing-Xing; Yuan, Ping; Zhao, Qin-Hua; Wu, Wen-Hui; Qiu, Hong-Ling; Luo, Ci-Jun; Gong, Su-Gang; Li, Hui-Ting; Zhang, Rui; He, Jing; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective Whether exercise-induced venous-to-systemic shunt (EIS) during cardiopulmonary exercise testing (CPET) has different manifestations or characteristics in idiopathic pulmonary arterial hypertension (IPAH) and chronic thromboembolic pulmonary hypertension (CTEPH) patients remains unknown. We explored the differences in hemodynamics, echocardiography, and prognosis between IPAH and CTEPH patients with and without EIS. Methods We conducted a retrospective cross-sectional cohort study and included 161 PH patients at Shanghai Pulmonary Hospital. Demographic, echocardiography, pulmonary hemodynamic, and CPET variables were compared between patients with and without EIS stratified by IPAH and CTEPH. EIS was determined by CPET. Binary logistic regression analyses were performed to explore independent influencing factors of EIS. Cox survival analysis was used to quantify the impact of EIS on the prognosis of patients. Results Exercise-induced venous-to-systemic shunt was found in approximately 17.4% of 86 IPAH patients and 20% of 75 CTEPH patients. All-cause mortality occurred in 43 (26.7%) patients during a median follow-up of 6.5 years. Compared with those without EIS, patients with EIS had higher peak end-tidal O2 and lower VO2/VE and tricuspid annular plane systolic excursion (TAPSE). Among the IPAH patients, EIS was associated with lower cardiac output, cardiac index, mixed venous oxygen saturation, VO2/VE, and TAPSE and higher VE/VCO2 and right ventricular end-diastolic transverse diameter. Logistic regression analysis indicated that VO2/VE was an independent factor influencing whether IPAH patients developed EIS during CPET. Cox logistic regression indicated that female IPAH patients or IPAH patients with higher VO2/VE and EIS had a better prognosis. Female IPAH patients had better 10-year survival. In IPAH patients without EIS, patients with higher VO2/VE had better 10-year survival. However, compared with CTEPH patients without EIS, those with EIS had similar echocardiographic, hemodynamic, CPET parameter results and 10-year survival. Conclusion Exercise-induced venous-to-systemic shunt exhibits different profiles among IPAH and CTEPH patients. Among IPAH patients, those with EIS had worse peak end-tidal O2, VO2/VE, and TAPSE than those without EIS. VO2/VE was an independent factor of EIS among IPAH patients. IPAH patients with EIS, female sex or higher VO2/VE had better survival. However, the association between EIS and PAH severity or prognosis in CTEPH patients needs to be further explored.